2018
DOI: 10.1186/s12913-018-3820-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of ambulance utilized patients in Addis Ababa, Ethiopia

Abstract: BackgroundWell organized and appropriately utilized pre-hospital emergency services play a critical role in augmenting emergency care systems. The primary objective of this study was to understand the demographic and clinical profile of patients who used ambulances in Addis Ababa. The secondary objectives were to assess ambulance response time, transport time and reasons for referral amongst inter-facility transported patients in Addis Ababa.MethodsThe study was designed as a cross-sectional retrospective char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
4
18
3
1
Order By: Relevance
“…Main indications for ambulance transfer were prolonged labor and hypertensive disorders, comparable to other studies from LICs [24,28]. This may be explained by poor quality of ANC leading to suboptimal knowledge of obstetric danger signs and low levels of birth preparedness and complication readiness (BP/CR) [29,30].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Main indications for ambulance transfer were prolonged labor and hypertensive disorders, comparable to other studies from LICs [24,28]. This may be explained by poor quality of ANC leading to suboptimal knowledge of obstetric danger signs and low levels of birth preparedness and complication readiness (BP/CR) [29,30].…”
Section: Discussionsupporting
confidence: 67%
“…In our setting, ambulances were mainly used to transfer pregnant women from low to higher level health facilities [21][22][23][24]. Our ambulance obstetric transfer rate of 3.7% was lower than those in other African studies that reported rates between 5% and 66% [21,24,25]. This could be explained by accompanying paramedics on ambulances providing support and triage of patients at the referring health facilities, preventing unnecessary referrals.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, studies conducted in Addis Ababa, Ethiopia, and Uganda found that ambulance services were used mostly for obstetric (labor) cases. 23,24 In response to the hypothetical scenarios (pedestrian hit by a car and a person with fall-down accident being hurt badly in a house) majority (46.2%) prefer ambulance as their preferred transport option in both scenarios, followed by 16% of Bajaj's. This finding is higher compared to a study conducted in Ghana where the majority of the respondents reported they would prefer a taxi.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced trauma care providers and specialty centers, including cardiac and trauma care, are increasing in number. But, it is reported that emergency patients are arriving to the treatment centers too late; after the golden hour has already passed or having already developed complications [5, 6].…”
Section: Introductionmentioning
confidence: 99%